'Situational awareness': Rethinking security in times of urban terrorism. (April 2019) - Krasmann, Susanne; Hentschel, Christine
The emergence of 'situational awareness' as a response to the perception of a new terrorism in European cities marks a significant shift in the conceptualization of security. Focusing on a recently introduced German Federal Police programme that trains ordinary officers in their capability to handle 'complex life-threatening situations of police operation', the article explores how situational awareness introduces a warrior logic into policing and urban subjectivity and modifies our understanding of security at large. It points us to the limitations of preparedness and concretizes the hitherto elusive call to resilience. Three analytical dimensions – space–time, sensing and connectivity – will be developed to render the situation thinkable for empirical research as well as to grasp security as a 'live' mode of government.